Strategi dan Dinamika Pelaksanaan Bimbingan Manasik Umrah dalam Meningkatkan Kesiapan Jamaah (Studi Kasus pada PT Wafdullah Tamu Mulia Cabang Bengkulu) - Sri Wahyu Ningsih; Yosy Arisandi; Evan Stiawan (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
The implementation of Umrah manasik guidance at PT Wafdullah Tamu Mulia Bengkulu Branch applies various strategies to prepare pilgrims, including systematic delivery of materials, practical simulations, personal approaches, the use of learning media, as well as mental and spiritual development. These methods aim to enhance the pilgrims’ understanding and readiness in performing the Umrah rituals. However, the instructors face several challenges related to the diverse backgrounds of the pilgrims, such as differences in educational levels, age, religious knowledge, and limited guidance time. These challenges require adjustments in teaching methods to effectively meet the needs of each pilgrim.